Complementing reversed-phase selectivity with porous graphitized carbon to increase the metabolome coverage in an on-line two-dimensional LC-MS setup for metabolomics. Issue 10 (21st May 2015) - Ortmayr, Karin; Hann, Stephan; Koellensperger, Gunda
<x xml:space="preserve">Abstract</x> A novel on-line combination of reversed phase and porous graphitized carbon liquid chromatography increases the versatility in non-targeted metabolomics.